Securing multimedia colour imagery using multiple high dimensional chaos-based hybrid keys. (1st January 2014) - Ahmad, Musheer; Ahmad, Tanvir
The rapid exchange of multimedia data over worldwide available internet and shared networks has encouraged its unauthorised access, illegal usage, disruption, alteration. Therefore, it demands efficient methods to provide security to multimedia contents for ensuring authorised access, preventing illegal disruption, alteration, etc. To meet the aforesaid needs, the authors propose an efficient encryption method to secure the multimedia colour imagery. Complex dynamic responses of multiple high-order chaotic systems are utilised to carry out image pixels shuffling and diffusion processes under the control of secret key. The pixels diffusion is done by randomly picking the actual encryption keys out of nine hybridised keys that are extracted from complex sequences of Chen, Rossler and Chua chaotic systems. Eventually, a high encryption effect is turned up in the encrypted multimedia colour images. Moreover, the shuffling and diffusion processes are made plain-image information dependent to resist the potential chosen-plaintext, chosen-ciphertext and known-plaintext attacks. The simulation results validate that the proposed method has great encryption performance and practicableness.